Management Enabling the Future Internet for Changing Business and New Computing Services 12th Asia-Pacific Network Operations and Management Symposium, APNOMS 2009 Jeju, South Korea, September 23-25, 2009 Proceedings - Hong, Choong Seon; Tonouchi, Toshio; Ma, Yan; Chao, Chi-Shih (Computer Communication Networks and Telecommunications, 2009)
This book constitutes the refereed proceedings of the 12th Asia-Pacific Network Operations and Management Symposium, APNOMS 2009, held in Jeju, South Korea in September 2009. The 41 revised full papers and 32 revised short papers presented were carefully reviewed and selected from 173 submissions. The papers are organized in topical sections on network monitoring and measurement, configuration and fault management, management of IP-based networks, autonomous and distributed control, sensor network and P2P management, converged networks and traffic, engineering, SLA and QoS management, active and security management, wireless and mobile network management, and security management.